Existence EXISTENCE OF NAHT METHOD IN THE DEVELOPMENT OF CONTEMPORARY ARABIC LANGUAGE - Athoillah Islamy (Taqdir, 2019)
One of the impacts of the development of science and technology is that it occurs in the development of various languages. This also happened to various terminology in Arabic. This study aims to find the significance of naht in the formation of various modern Arabic terminologies. This research is a qualitative research in the form of literature review. The data source of this research is various literatures on the study of naht in the formation of various terminologies in contemporary Arabic. The method of this research is qualitative descriptive analysis method. This study concludes that naht is a method of decapitation and summation of two or more words into one term (words). The existence of the naht pattern can provide great urgency related to the adaptation of Arabic in the development of language in the current modern global era, which can give birth to various new Arabic terminology.